2022
DOI: 10.1021/acs.jpclett.2c00844
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Pathway from CdSe Nanoplatelets with Absorption Doublets at 373/393 nm to Nanoplatelets at 434/460 nm

Abstract: For those colloidal semiconductor CdSe nanospecies that exhibit sharp optical absorption doublets, different explanations have appeared in the literature regarding their morphological nature and formation, with no consensus reached. Here, we discuss the transformation pathway in two types of CdSe nanoplatelets (NPLs), from NPL-393 to NPL-460, exhibiting absorption doublets at 373/393 and 433/460 nm, respectively. Synchrotronbased small/wide-angle X-ray scattering (SAXS/WAXS) was performed to monitor the in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…For example, a continuous red-shift behavior is expected when zero-dimension (0D) QDs grow in size due to monomer addition directly onto the mother QDs . On the other hand when a stepwise red-shift is observed, monomer addition has often been assumed to take place on CdSe 0D clusters to become larger or 2D nanoplatelets (NPLs) to become thicker. ,, This assumption infers that the intermediate does not have a measurable optical absorption, but it is difficult to understand why now. The difficulty disappears, however, when this assumption is abandoned and the concept of the PC-assisted transformation is applied.…”
Section: Lower Temperatures Promoting Step 2c To Complete Pathwaymentioning
confidence: 99%
“…For example, a continuous red-shift behavior is expected when zero-dimension (0D) QDs grow in size due to monomer addition directly onto the mother QDs . On the other hand when a stepwise red-shift is observed, monomer addition has often been assumed to take place on CdSe 0D clusters to become larger or 2D nanoplatelets (NPLs) to become thicker. ,, This assumption infers that the intermediate does not have a measurable optical absorption, but it is difficult to understand why now. The difficulty disappears, however, when this assumption is abandoned and the concept of the PC-assisted transformation is applied.…”
Section: Lower Temperatures Promoting Step 2c To Complete Pathwaymentioning
confidence: 99%
“…Then, they were mixed at room temperature; CdTeSe MSC-399 developed during the room-temperature incubation of the resultant mixture. We suggested that similar to binary MSCs, ternary CdTeSe MSC-399 also evolved from its counterpart PC, ternary CdTeSe PC-399, and PC-399 was produced via the substitution reaction of the CdTe PC and CdSe Mo/Fr . During the mixture incubation, PC-399 formed with a relatively fast rate and then transformed to MSC-399 at a relatively slow speed.…”
mentioning
confidence: 99%
“…Colloidal II–VI metal (M) and chalcogenide (E) semiconductor magic-size clusters (MSCs) have their own special precursor compounds (PCs). While MSCs display sharp optical absorption at constant wavelengths, their counterpart PCs are transparent at these and longer wavelengths. The idea that MSCs evolve from their corresponding PCs via intramolecular reorganization is present in the two-pathway model that provides an in-depth understanding of the growth relation between binary ME MSCs and binary colloidal semiconductor ME quantum dots (QDs) (Scheme S1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that the evolution of the CdS NPLs is due to the self-assembly of the CdS MSCs, similar to that suggested for CdSe (Figure S1-8A). [14,23] For the formation and transformation of PL semiconductor 2D NPLs, the PC-related (Figure S1-8A) and not PC-related (Figure S1-8B) pathways have been proposed; the present study does not address this ongoing issue.…”
Section: Pl Cds Msc-328 and Msc-373 Directly From A Cd(ma) 2 + S + Ho...mentioning
confidence: 82%